Does acupuncture treatment reduce temporomandibular dysfunction symptoms? - Vilela , Maria Cristina Ramos; Ramos , Carina Mabel de Albuquerque; Fernandes, Renata Silva Melo; David, Mírian Celly Medeiros Miranda; Silva, Valdir Luna da; Matos, Rhowena Jane Barbosa de (Acta Scientiarum. Health Sciences, 2024)
To analyze the pain, the muscle profile of some muscles actively and passively involved in the stomatognathic system, and stress traits. A clinical, randomized and double-blind study (n = 35) was performed analyzed by the Research Diagnostic Criteria/Temporomandibular Dysfunction (RDC/TMD), with subjects allocated in experimental group (EG) which received acupuncture at the meridian points according to Traditional Chinese Medicine, and another placebo group (PG) which received acupuncture at random points. The degree of discomfort was evaluated by the Visual Analog Scale (VAS), tissue sensitivity, somatic and psychic anxiety level, salivary cortisol levels, electrical activity of the masseter, anterior temporal, sternocleidomastoid (SCM) and trapezoid muscles before and after the proposed treatment. The Wilcoxon test, Chi-squared test, Signal test, Mann-Whitney U-test, paired and independent Student’s t-test, Pearson’s correlation test and the symmetry index of the muscles were used for statistical analysis, considering a significance level equal to 0.05. There was a reduction of physical non-specific TMD symptoms, and the degree of discomfort decreased by fifty percent in the EG, with a trend curve pointing to an evolution in the repair process. Tissue sensitivity decreased in the EG and increased in the PG. The treated group presented a reduction of physical and psychological manifestations in the anxiety situation, while the reduction was only for physical manifestations in the PG. Salivary cortisol levels did not change. The masticatory musculature presented an increase in the temporal activity and a decrease in the masseter/temporal ratio in the PG. The EG showed a better relationship between the trapezium and sternocleidomastoid muscles. Therefore, acupuncture treatment was efficient for reducing the pain symptoms and the physical and mental conditions of anxiety in people with TMD, as well as to improve the relationship of postural muscles.